Research on the mechanism of digital drive economy enhancing quality and efficiency - Ruixvan Gao; Jialun Lyu (PLoS ONE, 2025)
This paper, based on unstructured data, examines the outcomes and impact mechanisms of digitalization from the perspective of technological advancement and institutional evolution, providing empirical evidence for the role of digitalization in promoting economic quality and efficiency. The study finds that digitalization contributes to the improvement of regional economic development efficiency. Its economic impact primarily manifests in the transformation of traditional value creation models and the enhancement of marketization levels. The digital economy, by activating digital platforms, alleviates the problem of information asymmetry, thereby enhancing the standardization of market transactions and improving economic efficiency.